Characteristics of The Family Needs of Patients Who are Waiting for Their Family in The Icu Room of Efarina Etaham Hospital, Berastagi, Karo District, 2017 - Maswan (Science Midwifery, 2022)
The family is a very important support system in the patient's healing process. One contribution, the family has roles and functions, including recognizing the health problems of each family member, making decisions to take appropriate actions for the family, providing care to family members who are sick or who are not. can help themselves, maintain an atmosphere at home that is favorable to the health and personality development of family members, maintain reciprocal relationships between families and health institutions by utilizing existing health care facilities (Friedman, 2008). The purpose of this study was to determine the characteristics of the family needs of patients waiting for their families in the ICU room of Efarina Etaham Berastagi Hospital, Karo Regency in 2017. The research design used in this study is explorative descriptive. The population in this study was the entire family of patients who were waiting for their families in the ICU ward of Efarina Etaham Berastagi Hospital, Karo Regency for the period August 2016 - August 2017 as many as 1627 people. From the results of the study, all respondents expressed their views on information needs in the form of knowing the patient's disease progress (93"9), were given an explanation about the treatment plan (89"6), knew the ICU staff who provided care (595) and the results of the study all respondents said that they have a need for mental support in the form of getting the right answer from the ICU staff (86”9), there is a spiritual service in the ICU room (33Y40). expected to be input for management at the hospital in evaluating the service system, monitoring service quality, completing and maintaining facilities and regulatory policies in the ICU room related to the needs of the families of patients waiting for their families in the ICU ward which are needed as an effort to improve service to patients and family.